11.2Rt LRt LRt Leee−−−=−⇒=Taking the natural logarithm of both sides (and using lnln122bg=−) we obtain ln 2ln 2.RtLtLR⎛⎞=⇒=⎜⎟⎝⎠59. (a) We assume iis from left to right through the closed switch. We let i1be the current in the resistor and take it to be downward. Let i2be the current in the inductor, also assumed downward. The junction rule gives i = i1+ i2and the loop rule gives i1R – L(di2/dt) = 0. According to the junction rule, (di1/dt)= – (di2/dt). We substitute into the loop equation to obtain
This is the end of the preview. Sign up
access the rest of the document.
This note was uploaded on 06/03/2011 for the course PHY 2049 taught by Professor Any during the Spring '08 term at University of Florida.